How audit quality affects tax avoidance: an analytical study in Pakistan - Shafiq, Ume Salma; Selamat, Aslam Izah; Mohd Nor, Normaziah; Amin Noordin, Bany Ariffin (Human Resources Management Academic Research Society (HRMARS), 2024)
Substantial tax revenue is the lifeblood of a nation's growth and development, yet this essential resource is often undermined by individuals who choose to sidestep their obligations through various tax avoidance strategies. Despite the necessity of taxes for national progress, the reluctance of some to contribute willingly presents a significant challenge to achieving sustainable economic advancement. This study expects to inform the impact of audit quality and tax avoidance among Pakistani non-financial firms, which is investigated based on agency and signaling theory. The study adds to the current literature by examining how audit quality influences corporate tax avoidance activities. This study utilizes a unique dataset of the top 50 firms, spanning from 2016 to 2022, and uses panel data along with the FE and SGMM estimate technique for accounting for potential endogeneity; the study finds a significant positive link between audit quality and tax avoidance. The data show that higher audit quality is associated with lower tax avoidance, implying that rigorous audits discourage aggressive tax planning and improve financial reporting credibility. This study has important implications for policymakers and corporate governance specialists, highlighting the necessity of emphasizing audit quality to reduce tax avoidance. The study admits limitations, such as its concentration on non-financial enterprises in Pakistan, which may impact the conclusion's broader relevance. Future research should investigate this relationship across industries or geographies and consider other factors influencing tax avoidance, such as corporate governance systems.